Sistem Pendukung Keputusan Menggunakan Metode Profile Matching Untuk Penentuan Pemberian Kredit (Studi Kasus: KSP Werdhi Mekar Sari Sedana) - Sudipa, I Gede Iwan; Sudiani, Ni Made (INFOTEKS (Information Technology, Computer and Sciences), 2019)
The Mekar Sari Sedana Savings and Loan Cooperative is a cooperative that runs a business in the field of savings and loans as a business that provides credit to customers. In selecting prospective customers and giving decisions to customers who apply for credit by cooperative managers, the calculation of the value obtained by customers applying for credit is not based on criteria 5C, which is a requirement for lending to cooperatives. The method used in this research is Profile Matching a decision-making mechanism by comparing the value of data from a profile that will be assessed with the expected profile value, so that differences in accurate competency values ​​can be known. From the results of the blackbox testing conducted, it was found that the system that was built was in line with expectations and after the calculation of the profile matching method was tested manually and compared with the calculation results generated by the system with the results of manual calculations using the profile matching method.